Snap Bean Soil Fertility Program in Miami-Dade County - Monica Ozores-Hampton; Qiang Zhu; Yuncong Li (EDIS, 2015)
In terms of acreage, snap beans are the most commonly grown vegetable in Miami-Dade County. This 4-page fact sheet outlines the impact of fertilizer use and local weather and soil on snap bean production in this region. Written by Monica Ozores-Hampton, Qiang Zhu, and Yuncong Li, and published by the UF Department of Horticultural Sciences, May 2015.